2007
DOI: 10.1152/ajprenal.00281.2006
|View full text |Cite
|
Sign up to set email alerts
|

PAX2 is reactivated in urinary tract obstruction and partially protects collecting duct cells from programmed cell death

Abstract: Obstruction of the urinary tract activates apoptotic pathways in collecting duct cells and leads to loss of renal parenchyma before surgical intervention. It has been suggested that developmental pathways may be reactivated to offset acute organ damage. One such molecule, PAX2, is expressed throughout the fetal collecting duct and was recently shown to suppress apoptosis during kidney development. We hypothesized that acute unilateral urinary tract obstruction (UUO) reactivates PAX2 expression in the mature ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…To explain this Wnding, some speculations can be made on the basis of kidney investigations. It was suggested that the increased PAX2 expression in urinary tract obstructions can be related with the antiapoptotic role of PAX2, taking place to prevent atrophy [22]. The anti-apoptotic eVect of PAX2 was shown to be the result of the transcriptional activation of the neural apoptosis inhibitory protein gene [23].…”
Section: Discussionmentioning
confidence: 99%
“…To explain this Wnding, some speculations can be made on the basis of kidney investigations. It was suggested that the increased PAX2 expression in urinary tract obstructions can be related with the antiapoptotic role of PAX2, taking place to prevent atrophy [22]. The anti-apoptotic eVect of PAX2 was shown to be the result of the transcriptional activation of the neural apoptosis inhibitory protein gene [23].…”
Section: Discussionmentioning
confidence: 99%
“…Some work suggests that Pax2 uses the same set of functions during kidney repair as it does during development ( Figure 3). Particularly, it has been Page 18 of 36 A c c e p t e d M a n u s c r i p t found that Pax2 inhibits apoptosis of tubular renal cells during the initial stage of regeneration [115,118,119]. Other studies suggest that Pax2 may be implicated in epithelial to mesenchymal transition of epithelial tubular cells and confers a mesenchymal stem cell-like progenitor phenotype on those cells, which is required for proper re-differentiation during kidney repair [89,91,120].…”
Section: Adult Roles Of Pax2/8 Genes-implications In Kidney Regenerationmentioning
confidence: 99%
“…[30][31][32][33][34][35] We used TUNEL labeling to assay apoptosis in kidneys obstructed for 1, 2, 3, 6, and 9 days. In sham-operated kidneys at all time points, TUNEL-positive cells were rare and scattered throughout the kidney (Figures 4a-c) and are indicative of the normal rate of cell turnover within the kidney.…”
Section: Apoptosismentioning
confidence: 99%